2018
DOI: 10.1111/ejn.14126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the phase of force production on corticomuscular coherence with agonist and antagonist muscles

Abstract: During isometric contractions, the net joint torque stability is modulated with the force production phases, i.e., increasing (IFP), holding (HFP), and decreasing force (DFP) phases. It was hypothesized that this modulation results from an altered cortical control of agonist and antagonist muscle activations. Eleven healthy participants performed 50 submaximal isometric ankle plantar flexion contractions. The force production phase effect (IFP, HFP and DFP) was assessed on the net joint torque stability, agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Corticomuscluar coherence of the agonistic and antagonistic muscles was observed during sustained isometric elbow flexion (Bayram et al, 2015). Ushiyama et al (2011) and Desmyttere et al (2018) demonstrated that corticomuscular coherence was altered according to the contraction phases during isometric contractions. However, to our knowledge, no studies had explicitly quantified the relationship of coherence between flexors and extensors which acted as agonist during elbow isokinetic contraction stage.…”
Section: Discussionmentioning
confidence: 99%
“…Corticomuscluar coherence of the agonistic and antagonistic muscles was observed during sustained isometric elbow flexion (Bayram et al, 2015). Ushiyama et al (2011) and Desmyttere et al (2018) demonstrated that corticomuscular coherence was altered according to the contraction phases during isometric contractions. However, to our knowledge, no studies had explicitly quantified the relationship of coherence between flexors and extensors which acted as agonist during elbow isokinetic contraction stage.…”
Section: Discussionmentioning
confidence: 99%
“…Such information can hardly be obtained directly from power spectra, simply because-due to field spread-mu rhythms and activity from distinct but nearby neuronal populations cannot be separated based on their sensor topography. Considering this should help make sense of past and future research in which, e.g., CMC is measured with several agonist and antagonist muscles with the endeavour to unravel cortical motor control of skilled motor actions in health and impairment (Cremoux et al, 2017;Dal Maso et al, 2017;Desmyttere et al, 2018). Note also that based on MEG or EEG recordings, CMC estimated with a given muscle is affected by the~20-Hz mu activity in surrounding regions, and that a measure free from such contamination is the burstiness of~20-Hz EMG/force fluctuations (Bourguignon et al, 2017).…”
Section: Perspectivesmentioning
confidence: 99%
“…modulations of CMC in beta and gamma bands during different movement periods of simple movements, such as knee flexions 10 and ankle flexions 11 as well as during different stages of more compound gait cycles 12 , indicating frequency band related cortical oscillations to play a crucial role concerning flexible motor control.…”
mentioning
confidence: 99%